1998
DOI: 10.1093/ps/77.9.1306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tylosin tartrate (Tylan Soluble) on cellular immune responses in chickens

Abstract: Although many antimicrobial agents have been reported to cause immunosuppression in animals, macrolide antibiotics enhance immune function. Tylosin is a macrolide antibiotic approved for the control of mycoplasmosis in poultry. The purpose of this investigation was to determine the effect of tylosin on cellular immune functions in chickens. There was no significant difference in adherent splenocyte chemotaxis between tylosin-treated and untreated (control) chickens. Tylosin increased splenocyte proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Although no difference was seen concerning the circulating numbers of monocytes, tylosin could have had an effect on cytokine production by these cells, or could even have altered local (intestinal, for instance) macrophage populations, which can control circulating lymphocytes. Tylosin is indeed capable of altering the proliferative capacity of immune cells, thus explaining some of the findings of the present study (BABA et al, 1998).…”
Section: Cd4supporting
confidence: 83%
“…Although no difference was seen concerning the circulating numbers of monocytes, tylosin could have had an effect on cytokine production by these cells, or could even have altered local (intestinal, for instance) macrophage populations, which can control circulating lymphocytes. Tylosin is indeed capable of altering the proliferative capacity of immune cells, thus explaining some of the findings of the present study (BABA et al, 1998).…”
Section: Cd4supporting
confidence: 83%
“…Prior reports in avian systems support our observations of monensin-enhanced spleen cell proliferation. White Leghorn chickens that received a single oral dose of 140 mg/kg tylosin, a macrolide antibiotic that inhibits bacterial protein translation, exhibited increased ConA-stimulated spleen cell proliferation compared with untreated controls (Baba et al, 1998). Munir et al (2009) reported that the antibiotic ionophore salinomycin, when supplemented in the diet at a concentration of 66 ppm, enhanced phytohemagglutinin-induced proliferation of peripheral blood lymphocytes in young broiler chickens compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Tylosin was administered at 11 mg/kg twice a day during 28 days orally for cats infected by Cryptosporidium spp., and there was a remission of clinical signs in the first week of treatment (Lappin et al 1997). Tylosin is a macrolide with effects that are also immunomodulatory (Baba et al 1998). Since the animal had chronic diarrhea, the possibility of spontaneous healing is lower and tylosin efficacy, in this case, seems to be the most plausible hypothesis.…”
Section: Diagnosismentioning
confidence: 98%